Divine wisdom and human wisdom in The Divine Names by St. Dionysius the Areopagite - Savu Totu (Methexis)
In the writings of St. Dionysius the Areopagite, where the right faith in God is reflected by Christian philosophy with the greatest clarity, we will fully understand the abyssal difference between divine wisdom and human wisdom. As it was revealed to St. Paul the Apostle, for every Christian believer, this difference is normative for the configuration of the relationship between Greek philosophy and true faith in God. Therefore, having the “demonstration of the Spirit and power” (I Cor. 2:4) – the only source of the preaching of the Truth “in weakness and fear and in much trembling” (I Cor. 2:3) – through the image of the divine names, we will understand how we can acquire godly wisdom through the “third way” of the working of our reason and mind.